2012
DOI: 10.3846/16111699.2011.652980
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of the Financial Crisis on Insider Trading Profitability in Belgium

Abstract: The 2007 global financial crisis led to a chaotic financial environment characterized by highly uncertain and volatile stock markets. This created additional uncertainty about the fundamental value of shares and potentially increased the benefit of inside information. In this paper, we use event study methodology to examine whether Belgian corporate insiders were able to benefit from these turbulent market conditions. Given the large weight of financial institutions, the Belgian stock market was especially vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…The study by Lawrence (2013) revealed that higher quality financial disclosures by firms encourage individuals to risk and invest more. The importance of information access has also been confirmed by examining insiders who have access to relevant information about the firm's performance, in a study by Van Geyt et al (2013), shows that insiders benefit from inside information during financial crisis trading, and which resulted in higher profits.…”
Section: Discussionmentioning
confidence: 88%
“…The study by Lawrence (2013) revealed that higher quality financial disclosures by firms encourage individuals to risk and invest more. The importance of information access has also been confirmed by examining insiders who have access to relevant information about the firm's performance, in a study by Van Geyt et al (2013), shows that insiders benefit from inside information during financial crisis trading, and which resulted in higher profits.…”
Section: Discussionmentioning
confidence: 88%
“…Thin-trading describes situations where stocks do not trade for a prolonged period of time which is a prominent feature of stock markets in developing countries (Robinson, 2016; Watson, 2009), and is especially true of those in the Commonwealth Caribbean. Geyt, Cauwenberge and Bauwhede (2013) developed an approach to adjust the standard methodology for thin trading, and this study adopts this approach which improves the robustness of the results.…”
Section: Methodsmentioning
confidence: 99%
“…A TMT that includes executives with international experience tends to have a global mindset, which may have influenced the respective firm's strategic actions in response to the global financial crisis, thereby influencing the firm's resilient performance (Sambharya, 1996). Subindustry dummies were also controlled for because three subindustries of the electronics industry (i.e., computer and peripheral equipment manufacturing, communication technology manufacturing, and electronic solution product manufacturing) were included in the sample firms, and the global financial crisis may have imposed different effects on the distinct subindustries (Bricongne et al, 2012;Van Geyt et al, 2013). Table 1 provides descriptive statistics and correlation coefficients for the variables included in this study.…”
Section: Control Variablesmentioning
confidence: 99%
“…The proposed relationships were tested on a sample of 168 electronics firms in a newly industrialized economy. The global financial crisis compelled these firms to undergo sharp changes in the macro, industrial, and competitive environments and tested each firm's capacity to withstand the resulting global economic turmoil (Bricongne, Fontagne, Gaulier, Taglioni, & Vicard, 2012;Sabatino, 2016;Van Geyt, Van Cauwenberge, & Vander Bauwhede, 2013). This paper offers several unique contributions to the relevant upper-echelon literature.…”
Section: Introductionmentioning
confidence: 99%